The first described fossil species of Litargus Erichson (Coleoptera: Mycetophagidae) from Eocene Baltic amber examined with X-ray microtomography, and new records of Crowsonium succinium Abdullah, 1964 - Alekseev, Vitalii I.; Kupryjanowicz, Janusz; Kairišs, Kristaps; Bukejs, Andris (Zootaxa, 2020)
A new species of Mycetophagidae belonging to the genus Litargus, namely L. (Litargosomus) dantiscensis Alekseev, Kupryjanowicz et Bukejs sp. nov., is described and figured from Eocene Baltic amber using X-ray micro-computed tomography (μCT). Three additional specimens of a mycetophagid beetle that is rather common in Baltic amber, Crowsonium succinium Abdullah, are also reported. Prototoma striata Heer, which was originally placed in Mycetophagidae, is discussed based on its original description and illustration: it is proposed that the position incertae sedis within Coleoptera be given to this Early Jurassic fossil. Consequently, the records of Mycetophagidae from Eocene European amber should be considered the earliest occurrence of the family known to date.